Burden of cancers attributable to modifiable risk factors in Malaysia - H. S. Teh; Y. L. Woon (BMC, 2021)
Abstract Background This is a systematic assessment of the burden of cancers in Malaysia in 2018 using epidemiologic approach. The purpose of this study was to identify the proportion of cancers in Malaysia that were attributable to the modifiable risk factors of excess weight, alcohol intake, physical inactivity, tobacco smoking and to estimate the number of cancer cases that could be prevented if the exposure to the modifiable risk factor was reduced. Methods We estimated the Population Attributable Fraction (PAF) of the modifiable risk factors to cancers incidences in Malaysia. The two parameters used for the estimation were exposure prevalence from national representative surveys and the relative risk of getting the cancers from worldwide literature review. Results Among 38,426 cancer incidences in 2018 from Globocan data, we estimated that 22.2% (95% confidence interval (CI):14.9 to 29.6%) of the cancer incidences included in this study were attributable to the investigated modifiable risk factors. 39.1% (95% CI:27.2 to 49.7%) and 10.5% (95% CI:5.8 to 15.7%) of cancers in male and female respectively, were attributable to the studied modifiable risk factors. The top main cancers attributed by the risk factors were lung cancer (65.1%; 95% CI:56.4 to 72.9%), laryngeal cancer (63.6%; 95% CI:39.9 to 80.5%), and oesophageal cancer (51.5%; 95% CI:39.9 to 62.0%). For each risk factor studied across genders, tobacco smoking contributed the most (14.3%; 95% CI:9.9 to 17.3%), followed by excess weight (7.0%; 95% CI:4.1 to 10.2%), physical inactivity (1.0%; 95% CI:0.4 to 1.7%) and alcohol intake (0.6%; 95% CI:0.2 to 1.0%). Conclusion Findings from this study suggests that tobacco smoking and excess weight are the two predominant factors out of the four studied risk factors for cancer cases in Malaysia. Nationwide public health prevention campaigns tailored to these risk factors are recommended. However, the other risk factors such as physical inactivity and alcohol intake shall not be neglected. PAFs are estimated based on the best available data that we have currently. Regular collection of other risk factor exposure prevalence data is vital for future analyses.